Focality in Febrile Seizures: A Retrospective Assessment Using Arterial Spin Labeling MRI - Yeom, Jung Sook; Kim, Young-Soo; Choi, Dae-Seob (Neuropediatrics, 2023)
Purpose Defining focality of febrile seizures (FS) in clinical practice remains controversial. We investigated focality issues in FS with a postictal arterial spin labeling (ASL) sequence.Methods We retrospectively reviewed 77 children (median: 19.0 months, range: 15.0–33.0 months) who consecutively visited our emergency room for FS and underwent brain magnetic resonance imaging (MRI), including the ASL sequence, within 24 hours of seizure onset. ASL data were visually analyzed to assess perfusion changes. Factors related to the perfusion changes were investigated.Results The mean time to ASL acquisition was 7.0 (interquartile range: 4.0–11.0) hours. The most common seizure classification was unknown-onset seizures (n = 37, 48%), followed by focal-onset (n = 26, 34%) and generalized-onset seizures (n = 14, 18%). Perfusion changes were observed in 43 (57%) patients: most were hypoperfusion (n = 35, 83%). The temporal regions were the most common location of perfusion changes (n = 26, 60%); the majority of these were distributed in the unilateral hemisphere. Perfusion changes were independently associated with seizure classification (focal-onset seizures, adjusted odds ratio [aOR]: 9.6, p = 0.01; unknown-onset seizures aOR: 10.4, p < 0.01), and prolonged seizures (aOR: 3.1, p = 0.04), but not with other factors (age, sex, time to MRI acquisition, previous FS, repeated FS within 24 hour, family history of FS, structural abnormality on MRI, and developmental delay). The focality scale of seizure semiology positively correlated with perfusion changes (R = 0.334, p < 0.01).Conclusion Focality in FS may be common, and its primary origin might be the temporal regions. ASL can be useful for assessing focality in FS, particularly when seizure onset is unknown.
Keywords: febrile seizures; magnetic resonance imaging; perfusion imaging